2013
DOI: 10.1016/j.wombi.2013.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Reimagining the General Health Questionnaire as a measure of emotional wellbeing: A study of postpartum women in Malta

Abstract: Findings generally support the reliability and validity of the Maltese version of the GHQ-12(WB). Model fit changes over time reflect the dynamic nature of postpartum recovery. Further evaluation of the GHQ-8(WB) is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 35 publications
2
13
0
Order By: Relevance
“…Each item was rated 0, 0, 1, and 1 (“better than ever,” “same as ever,” “worse than ever,” or “much worse than ever”). A total score of 2 on this test suggests a “probable mental health problem.” The GHQ has been shown to have satisfactory psychometric properties among women in their third trimester of pregnancy and postnatal period in China and Malta (Ip & Martin, ; Spiteri, Jomeen, & Martin, ).…”
Section: Methodssupporting
confidence: 84%
See 1 more Smart Citation
“…Each item was rated 0, 0, 1, and 1 (“better than ever,” “same as ever,” “worse than ever,” or “much worse than ever”). A total score of 2 on this test suggests a “probable mental health problem.” The GHQ has been shown to have satisfactory psychometric properties among women in their third trimester of pregnancy and postnatal period in China and Malta (Ip & Martin, ; Spiteri, Jomeen, & Martin, ).…”
Section: Methodssupporting
confidence: 84%
“…The GHQ has been shown to have satisfactory psychometric properties among women in their third trimester of pregnancy and postnatal period in China and Malta (Ip & Martin, 2006;Spiteri, Jomeen, & Martin, 2013 questions for each of 7 substance groups: alcohol, tobacco, cannabis, stimulants, sedatives, opioids, and other substances. For each of these, the ASSIST-Lite is scored: "not used in the past three months" (0), "used, but no other items positive" (1), "used and either test item positive" (2), and "used and both items positive" (3).…”
Section: The General Health Questionnairementioning
confidence: 99%
“…On the other hand, when analyzing studies in the field of obstetrics, this emotion is only described in qualitative studies on obstetric violence, reaching the conclusion that pregnant women were unsatisfied with the care they received during childbirth. (7,(16)(17)(18) Ekman & Rosenberg (11) claim that "anger" controls, punishes, and retaliates. Thus, how can we imagine "anger" as the most present emotion in all childbirths in this study?…”
Section: Discussionmentioning
confidence: 99%
“…(1,18,19) Considering that humanity is only possible thanks to the primal and physiological event of childbirth, since nobody is born otherwise, the association that childbirth involves "anger" can be made. For a woman to physiologically consent her child to be born, she needs to rescue her animal side, the mammalian that exists within her body, regardless of her intellectual evolution.…”
Section: Discussionmentioning
confidence: 99%
“…The most extensively validated measure was the GHQ but the results suggest it has poor validity in early years parenting samples. There were discrepancies reported in the structure of the GHQ, with 2 studies finding a 2-factor model to offer a superior fit to the data (Ip & Martin, 2006;Spiteri, Jomeen, & Martin, 2013) suggesting it may not be a unitary measure of psychological wellbeing. Furthermore, Aderibigbe and Gureje (1992) found that only 3 of the 4 subscales of the GHQ made a significant contribution to the discriminatory power of the GHQ.…”
Section: General Health Questionnairementioning
confidence: 99%